Simultaneous binding of PtdIns(4,5)P2 and clathrin by AP180 in the nucleation of clathrin lattices on membranes. - Ford, MG; Pearse, B; Higgins, M; Vallis, Y; Owen, D; Gibson, A; Hopkins, C; Evans, P; McMahon, H (2001)
Adaptor protein 180 (AP180) and its homolog, clathrin assembly lymphoid myeloid leukemia protein (CALM), are closely related proteins that play important roles in clathrin-mediated endocytosis. Here, we present the structure of the NH2-terminal domain of CALM bound to phosphatidylinositol-4,5- bisphosphate [PtdIns(4,5)P2] via a lysine-rich motif. This motif is found in other proteins predicted to have domains of similar structure (for example, Huntingtin interacting protein 1). The structure is in part similar to the epsin NH2-terminal (ENTH) domain, but epsin lacks the PtdIns(4,5)P2-binding site. Because AP180 could bind to PtdIns(4,5)P2 and clathrin simultaneously, it may serve to tether clathrin to the membrane. This was shown by using purified components and a budding assay on preformed lipid monolayers. In the presence of AP180, clathrin lattices formed on the monolayer. When AP2 was also present, coated pits were formed.